Cry of the wolf - Spencer, Zane 1935-; Leech, Jay 1931-. (Philadelphia Westminster Press, 1977)
Crippled from an auto accident in which his father was killed, Jim must rise above his sense of guilt and worthlessness to assume some of the responsbilities on the family's failing ranch.
Keywords: Ranch life -- Fiction; People with disabilities -- Fiction